Competing Transport Networks - Marco J. van der Leij (Tinbergen Institute, 2003)
In a circular city model, I consider network design and pricing decisions for asingle fast transport connection that faces competition from a slower but betteraccessible transport mode. To access the fast transport network individuals haveto make complementary trips by slow mode. This fact has interesting implicationson the location decisions. I show that in the presence of competition the profit-maximizingand socially optimal decision would be to cluster the two stations. Bycontrast, in the absence of competition both a profit-maximizing firm and a socialplanner would locate the two stations on opposite sides of the circle.
Keywords: L91; D40; 330; Networks; Transportation; Competition; Market area; Circular city.; Verkehrsträgerwettbewerb; Verkehrsteilung; Verkehrsweg; Theorie